PEMBELAJARAN LINGKARAN DENGAN METODE DEMONSTRASI MELALUI ALAT PERAGA KONKRIT DAN ALAT PERAGA GAMBAR - ., Nurmitasari (JURNAL E-DUMATH, 2016)
This research aimed to determine: 1) the average difference of mathematicsstudents learning achievement through demonstration method between usingconcrete props and picture props. 2) The average results of the mathematicsstudents learning achievement through demonstration method using concreteprops are higher than picture props. This research was comparative research withthe population taken all of the students in the sixth grade of the first semester MIRaudlatul Munawwarah in the academic year 2014-2015. The sampling techniquewas using random cluster sampling technique. The research instrument used essaytests consists of 5 items essay with the data analysis using t-test. Based on thehypothesis testing, it can be concluded that the average results of the mathematicsstudents learning achievement through demonstration method using concreteprops is higher than using picture props, with the students learning achievementaverage obtained respectively 65.68 and 57.50.Keywords: demonstration method using concrete props, students learningachievement